Effects of forest proximity and socio-ecological determinants on tree species composition, diversity and carbon stocks in the Vhembe Biosphere Reserve in South Africa - Chirwa, Paxie W. (University of Pretoria, 2023)
Thesis (PhD (Forest Science))--University of Pretoria, 2023.